Nikon D3000 : from snapshots to great shots - Revell, Jeff (Peachpit, 2010)
Nikon's new D3000 is a perfect entry-level DSLR. This book is for anyone who upgrades from their point-and-shoot, or for anyone who wants to jump into photography with the control and capabilities of a DSLR but without the high price. There's the manual, of course, as well as competing books, and while they all explain, often in 400+ pages, what the camera can do, none of them shows exactly how to use the camera to create great images! This book has one goal: to teach D3000 owners how to make great shots using their Nikon camera. It teaches how to use the D3000 to create the type of photos that inspired users to buy the camera in the first place. Everything in the book is in service of creating a great image. Starting with the top ten things needed to know about the camera, photographer Jeff Revell then carefully guides readers through the modes of the camera. Users get practical advice from a pro on which settings to use when, great shooting tips, and even end-of-chapter assignments.